Pengaruh Investment Opportunity Set, Intangible Asset, Dan Sales Growth Terhadap Nilai Perusahaan - Ike Sultonah; Yunita Kurnia Shanti (CV. ITTC INDONESIA, 2025)
This research aims to empirically prove the investment opportunity set, intangible assets, and sales growth on company value. This research was conducted at a primary consumer goods industry company. The type of research used is quantitative with an associative method approach. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (BEI) for the period 2018 - 2023. Samples were collected using the purposive sampling method. The amount of data observed was 112 companies, so that 15 companies or 90 observation data were obtained. Data were processed using the Eviews 9 Statistical Program to test hypotheses using panel data regression analysis. The results of the research show that investment opportunity set, intangible assets and sales growth simultaneously influence company value, then partial testing shows that investment opportunity set and intangible assets influence company value, but partial sales growth does not influence company value.